Quotatives : new trends and sociolinguistic implications - Buchstaller, Isabelle (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2014)
"Quotatives considers the phenomenon "quotation" from a wealth of perspectives. It consolidates findings from different strands of research, combining formal and functional approaches for the definition of reported discourse and situating the phenomenon in a broader typological and sociolinguistic perspective. Provides an interface between sociolinguistic research and other linguistic disciplines, in particular discourse analysis, typology, construction grammar but also more formal approaches Incorporates innovative methodology that draws on discourse analytic, typological and sociolinguistic approaches Investigates the system both in its diachronic development as well as via cross-variety comparisons Presents careful definition of the envelope of variation and considers alternative definitions of the phenomenon "quotation" Empirical findings are reported from distribution and perception data, which allows comparing and contrasting perception and reality "--
Includes index.
Machine generated contents note: Acknowledgments Chapter 1 Introduction: What's new about the new quotatives? Chapter 2 You can quote me on that: Defining quotation Chapter 3 Variation and change in the quotative system: The global versus the local Chapter 4 Quotation across the generations: A short history of speech and thought reporting Chapter 5 Ideologies and attitudes to newcomer quotatives Chapter 6 Lessons learned from research on quotation Appendix 1 Linear regression analysis investigating the conditioning factors on the quotative system in the US and the UK Appendix 2 Alternative Cross-Tabulations Appendix 3 Social Attitudes Survey.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Quotation; Speech acts (Linguistics); Intercultural communication; Semantics; Sociolinguistics; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Sociolinguistics; Intercultural communication; Quotation; Semantics; Sociolinguistics; Speech acts (Linguistics); Electronic books